High-Quality Visual Experience Creation, Processing and Interactivity of High-Resolution and High-Dimensional Video Signals - Mrak, Marta; Grgic, Mislav; Kunt, Murat; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Last few years have seen rapid acceptance of high-definition television (HDTV) technology around the world. This technology has been hugely successful in delivering more realistic television experience at home and accurate imaging for professional applications. Adoption of high definition continues to grow as consumers demand enhanced features and greater quality of content. Following this trend, natural evolution of visualisation technologies will be in the direction of fully realistic visual experience and highly precise imaging. However, using the content of even higher resolution and quality is not straightforward as such videos require significantly higher access bandwidth and more processing power. Therefore, methods for radical reduction of video bandwidth are crucial for realisation of high visual quality. Moreover, it is desirable to look into other ways of accessing visual content, solution to which lies in innovative schemes for content delivery and consumption. This book presents selected chapters covering technologies that will enable greater flexibility in video content representation and allow users to access content from any device and to interact with it.
Quality of Visual Information -- Automatic Prediction of Perceptual Video Quality: Recent Trends and Research Directions -- Quality of Experience for High Definition Presentations - Case: Digital Cinema -- Quality of Visual Experience for 3D Presentation - Stereoscopic Image -- Video Coding for High Resolutions -- The Development and Standardization of Ultra High Definition Video Technology -- Compression Formats for HD Recording and Production -- Super Hi-Vision and Its Encoding System -- A Flexible Super High Resolution Video CODEC and Its Trial Experiments -- Mathematical Modeling for High Frame-Rate Video Signal -- Visual Content Upscaling -- Next Generation Frame Rate Conversion Algorithms -- Spatiotemporal Video Upscaling Using Motion-Assisted Steering Kernel (MASK) Regression -- Temporal Super Resolution Using Variational Methods -- Synthesizing Natural Images Using Spatial Layout Information -- 3D Visual Content Processing and Displaying -- The Use of Color Information in Stereo Vision Processing -- 3D Object Classification and Segmentation Methods -- Three-Dimensional Video Contents Exploitation in Depth Camera-Based Hybrid Camera System -- Improving 3D Visual Experience by Controlling the Perceived Depth Distortion -- 3D Visual Experience -- 3D Holoscopic Imaging Technology for Real-Time Volume Processing and Display -- Accessing Technologies for Visual Content -- Video Streaming with Interactive Pan/Tilt/Zoom -- End-to-End Management of Heterogeneous Environments Enabling Quality of Experience -- Quality-Driven Coding and Prioritization of 3D Video over Wireless Networks -- Scalable Indexing of HD Video -- Stereo Correspondence in Information Retrieval.
Keywords: Engineering; Computer vision; Microwaves; Telecommunication; Engineering; Microwaves, RF and Optical Engineering; Communications Engineering, Networks; Computer Imaging, Vision, Pattern Recognition and Graphics; Signal, Image and Speech Processing; Optics, Optoelectronics, Plasmonics and Optical Devices